The evaluation of children with prolonged cough accompanied by American College of Chest Physicians guidelines. (27th October 2013) - Karabel, Müsemma; Kelekçi, Selvi; Karabel, Duran; Gürkan, Mehmet Fuat
Abstract Introduction In children, coughs lasting longer than 4 weeks are considered to be chronic, with etiological factors varying widely. Objective This study included children with chronic cough who were followed for 1 year. All cases were evaluated with the guidance of the American College of Chest Physicians (ACCP), and etiological factors were analyzed. Methods The study included 270 children between the ages of 2 months and 14 years. Their presenting symptoms, physical examination findings and laboratory data were recorded. All patients underwent laboratory tests including direct chest X‐ray and spirometric measurements. Several patients required additional advanced examinations such as a sweat test, determination of immunoglobulin levels and bronchoscopy. Patients were reevaluated according to ACCP recommendations, and etiological factors were investigated. Results The total of 270 patients were included in the study included 43.3% (n = 153) females with a mean age of 6.5 ± 2.3 years (7 months to 17 years). After a 1‐year follow‐up of patients, we determined that the most common etiologic factors were asthma (27%), asthma‐like syndrome (15.5%) and gastroesophageal reflux (10%). Other etiological factors included upper airway cough syndrome and protracted bronchitis, respectively. Conclusion The use of a standardized clinical approach such as the ACCP increases the possibility for fast and accurate diagnosis during the treatment of children with chronic cough, and the use of these guidelines should be required.